Fatigue and primary biliary cirrhosis: association of globus pallidus magnetisation transfer ratio measurements with fatigue severity and blood manganese levels. (11th March 2004) - Forton, D M; Patel, N; Prince, M; Oatridge, A; Hamilton, G; Goldblatt, J; Allsop, J M; Hajnal, J V; Thomas, H C; Bassendine, M; Jones, D E J; Taylor-Robinson, S D
Abstract : Background and aim: Fatigue is the commonest symptom in primary biliary cirrhosis (PBC), affecting individuals at all stages of disease. The pathogenesis of fatigue in PBC is unknown although rat models suggest a central nervous system (CNS) cause. We examined the hypothesis that a CNS abnormality related to cholestasis, rather than cirrhosis per se, underlies this symptom. Patients and methods: Fourteen patients with precirrhotic PBC (stage I–II disease), four patients with stage III–IV PBC, and 11 healthy women were studied using cerebral magnetisation contrast imaging and proton magnetic resonance spectroscopy (MRS). Results: The globus pallidus magnetisation transfer ratio (MTR), a quantifiable tissue characteristic that may be abnormal in the presence of normal magnetic resonance imaging, was significantly reduced in precirrhotic PBC patients compared with healthy controls. These measurements correlated with blood manganese levels and were more abnormal in the more fatigued subjects. There were no differences in MRS measurements between the three study groups, suggesting that the abnormal MTR was not related to hepatic encephalopathy. Conclusion: This study suggests that impairments in liver function in PBC may adversely affect the brain long before the development of cirrhosis and hepatic encephalopathy, possibly as a result of altered manganese homeostasis within the CNS.